Experimentação e fatores associados ao tabaco e álcool entre adolescentes brasileiros : Pesquisa Nacional de Saúde do Escolar (PeNSE, 2015/2019) - Freitas, Elisângela Antônio de Oliveira (2023)
Adolescence is the phase of life that undergoes several changes in the physiological, psychological and social spheres that drive young people to seek new experiences and an adaptation among their peers, which provides exposure to various health risk situations, such as tobacco and alcohol experimentation. Objective: to analyze the prevalence of alcohol and tobacco experimentation and its association with sociodemographic, family, mental health, and behavior and lifestyle variables in Brazilian adolescents enrolled in public and private schools, between 2015 and 2019. Methods: Cross-sectional study, with data from the National School Health Survey of 2015 and 2019. The sample consisted of adolescents from all over Brazil. The outcome variables were alcohol and tobacco experimentation. Independent variables were presented in four hierarchical blocks, based on sociodemographic, family, mental health, behavior and lifestyle characteristics. Results: As products of the thesis, four manuscripts were produced. Manuscript 01: a greater number of risk factors was evidenced in block IV, consisting of behavior and lifestyle habits, which were shown to be associated with tobacco experimentation (p<0.001), with higher prevalence ratios (3.41 and 2.03, respectively, for drug experimentation and sexual intercourse). Manuscript 2: the variables that presented the highest adjusted prevalence ratios were experimentation with illicit drugs (ARP = 1.33) and sexual intercourse (ARP = 1.51). Manuscript 03: remained associated in the final model, most of the factors of the blocks considered, with statistical significance (p<0.001). Manuscript 04: the variables behavior and life habits showed the highest prevalence ratios for experimenting with illicit drugs (1.25) and sexual intercourse (1.50) and remained associated in the final model, most of the factors of the blocks considered, with statistical significance (p<0.001). Conclusion: experimentation with tobacco and alcohol among schoolchildren proved to be high and associated with sociodemographic, family, mental health, behavior and lifestyle factors. The need to involve the school and society in actions aimed at preventing experimentation with these substances among adolescents was evident.